Student radiographers' attitudes towards the older patient: Six and twelve months post intervention. Issue 2 (May 2016) - Kada, S.; Booth, L.
Abstract: Purpose: To design and evaluate the effects of an educational intervention on Norwegian student radiographer attitudes towards older people. Design: A longitudinal study design, using pre-test and post-test data was used to determine student attitudes to older people across their educational tenure. Attitudes were measured using Kogan's attitudes towards older people scale. This paper, the second in the series, reports on the changes in student radiographer attitudes, post an educational intervention and post their first experience of clinical placement. Results: Although students initially demonstrated significantly improved attitudes towards older people (p = 0.01), this significance was not noted at 6 months and 12 months post intervention. In fact average scores reduced to an almost identical level to those found pre-intervention Conclusion: Whereas an educational intervention can have an initial positive effect on student attitudes towards older people, the experience of clinical placement reduces these initial effects. Highlights: Reports the effects of an intervention to improve attitudes to older people. Pre-intervention students had generally positive attitudes to older people. Post-intervention attitudes were significantly more positive. At 6 months and 12 months post-intervention mean positive scores were reduced. Some questions score significantly more negatively than others.